On the holy - Sodeika, Tomas (Religija ir kultūra, 2011)
At the beginning of the 20th century the term “holy” has emerged in the vocabulary of philosophers, sociologists and the historians of religions. Common characteristics of these different interpretations were recognition that the holy is the ultimate total value and meaning of life and as such must be opposed to the profane. Besides the opposition of holy / profane, however, the holy includes some immanent opposition of a positive, vitalizing power and a danger that implicate rigorous prohibition against the touching the holy objects. The main aim of the article is to show that last mentioned dichotomy is fundamental feature of the holy.
Keywords: the holy; phenomenology of religion